Muscular anatomy of the forelimb of tiger (Panthera tigris). Issue 1 (2nd February 2022) - Dunn, Rachel H.; Beresheim, Amy; Gubatina, Ariel; Bitterman, Kathleen; Butaric, Lauren; Bejes, Katelyn; Kennedy, Sarah; Markham, Sam; Miller, Dustin; Mrvoljak, Midhad; Roge‐Jones, Lorraine; Stumpner, Jessica; et al.
Abstract: Dissection reports of large cats (family Felidae) have been published since the late 19th century. These reports generally describe the findings in words, show drawings of the dissection, and usually include some masses of muscles, but often neglect to provide muscle maps showing the precise location of bony origins and insertions. Although these early reports can be highly useful, the absence of visual depictions of muscle attachment sites makes it difficult to compare muscle origins and insertions in living taxa and especially to reconstruct muscle attachments in fossil taxa. Recently, more muscle maps have been published in the primary literature, but those for large cats are still limited. Here, we describe the muscular anatomy of the forelimb of the tiger ( Panthera tigris ), and compare muscle origins, insertions, and relative muscle masses to other felids to identify differences that may reflect functional adaptations. Our results reiterate the conservative nature of felid anatomy across body sizes and behavioral categories. We find that pantherines have relatively smaller shoulder muscle masses, and relatively larger muscles of the caudal brachium, pronators, and supinators than felines. The muscular anatomy of the tiger shows several modifications that may reflect an adaptation to terrestrial locomotion and a preference for large prey. These include in general a relatively large m. supraspinatus (shoulder flexion), an expanded origin for m. triceps brachii caput longum, and relatively large m. triceps brachii caput laterale (elbow extension), as well as relatively large mm. brachioradialis, abductor digiti I longus, and abductor digiti V. Muscle groups that are well developed in scansorial taxa are not well developed in the tiger, including muscles of the cranial compartment of the brachium and antebrachium, and m. anconeus. Overall, the musculature of the tiger strongly resembles that of the lion ( Panthera leo ), another large‐bodied terrestrial large‐prey specialist. Abstract : We describe the muscular anatomy of the tiger forelimb, and compare muscle origins, insertions, and relative muscle masses to other felids. Our results reiterate the conservative nature of felid anatomy across body sizes and behavioral categories. We find several differences in regional muscle mass between the two felid subfamilies, Pantherinae and Felinae, and identify modifications of tiger musculature that may reflect an adaptation to terrestrial locomotion and a preference for large prey.